Patterns of prescription antihypertensive drug utilization and adherence to treatment guidelines in the city of Novi Sad - Tomas, Ana; Tomić, Zdenko; Milijašević, Boris; Ban, Milica; Horvat, Olga; Vukmirović, Saša; Sabo, Ana (Vojnosanitetski pregled, 2017)
Background/Aim. Hypertension is one of the leading causes of cardiovascular morbidity and mortality and more than a half of all health insurance expenditures for reimbursed medicines are allocated to antihypertensive drugs in Serbia. The aim of this study was to identify the antihypertensive drug utilization patterns among hypertensive outpatients in the city of Novi Sad, Serbia, determine the adherence to clinical guidelines and address the economic aspects of current prescribing practices. Methods. This retrospective observational study was conducted in Novi Sad over a period of six months. The data on the number of packages, size their, and retail price of antihypertensives issued on prescription in outpatients with the diagnosis of essential arterial hypertension was collected from all state-owned pharmacies in Novi Sad. Drug consumption was analyzed using the Anatomical Therapeutic Chemical (ATC)/ deﬁned daily dose (DDD) methodology. Results. Total consumption of antihypertensives issued on prescription over a 6-month period in the city of Novi sad, Serbia was 283.48 DDD per 1,000 inhabitans per day (DID). Angiotensin converting enzyme inhibitors (ACEi) were most commonly prescribed drugs, and were used 3 times more often than calcium channel blockers and 5 times more than beta-blockers. The consumption of diuretics and angiotensin receptor antagonists was low within all the groups of outpatients. Both national and international guidelines state superiority and effectiveness of diuretics in treatment of hypertension in the elderly, but their consumption was unreasonable low despite the fact that over 70% of all antihypertensive drugs in the city of Novi Sad were dispensed in people aged > 60. The use of more expensive ACEi was observed despite the guidelines deeming all the drugs of this class equally effective in treatment of hypertension. Conclusion. Large differences in utilization of different groups of antihypertensive agents were noted in this study. Underutilization of valuable, efficacious, and cost-effective thiazide diuretics and overuse of expensive ACE inhibitors is unjustifiable. There is a potential for large savings with switching to low-price ACEi, modeling the practice of Scandinavian countries.